Keynesian parables of thrift and hoarding. (January 2016) - Rowe, Nicholas
Abstract : I argue that Keynes missed seeing the importance of the distinction between saving in the form of money ('hoarding') and saving in all other forms ('thrift'). It is excessive hoarding, not excessive thrift, that causes recessions and the failure of Say's law. The same failure to distinguish hoarding from thrift continues from The General Theory into the IS–LM model and into New Keynesian macroeconomics. On this particular question, economists should follow Silvio Gesell rather than John Maynard Keynes. The rate of interest in New Keynesian models should be interpreted as a negative Gesellian tax (that is, a subsidy) on holding money issued by the central bank.